(untitled) - Huff, Priscilla Y. (Hoboken, N.J., 2007)
If you’re an entrepreneur, or you’re just thinking of starting a business, start with this smart, practical guide to small business success. It shows you how to maintain healthy growth and profits—no matter what kind of business you own—and helps you get the most out of your limited resources. Grow your business and get on the fast track to success.
Keywords: Home-based businesses,Small business marketing,Doanh nghiệp tại nhà,Tiếp thị của doanh nghiệp nhỏ; Management,Quản lý